The effect of context and drivers' age on highway traffic signs comprehension. (August 2015) - Ben-Bassat, Tamar; Shinar, David
Highlights: We presented 28 road signs, to young and older drivers in context and without it. We tested the effect of drivers' age and sign context on sign comprehension accuracy and response time. Younger drivers performed significantly better than older drivers on both measures. Context had no effect on comprehension accuracy of either group, but increased response time. Response times of correct meaning were similar to response times of opposite to sign's meaning. Abstract: Background: Comprehension of traffic signs is crucial to safety. Objectives: To test the effects of the presentation condition (with or without driving context) on symbolic based road signs comprehension and comprehension time for young and older drivers. Method: 50 young drivers and 50 older drivers were presented with images of 28 Israeli road signs, both without context (with a white background) and in context (with the driving surrounding). Data were collected on the accuracy of signs meaning and on the time it took the participants to provide the meaning. Results: Younger drivers performed significantly better than older drivers on both accuracy and response time (RT). Older drivers' average RT was approximately twice as long as younger drivers' RT. However, the presentation mode (with or without context) did not affect sign comprehension of either group, but the presence of the context did increase the time it took the drivers to comprehend the sign's meaning. In addition, correct response time was similar to opposite to sign's meaning response time. Implications: Older drivers, can benefit from retraining in sign comprehension of current signage. The training should involve signs in their natural road environment to reduce comprehension time while actually driving. Moreover, signs that were understood as having an opposite meaning should be redesigned or be accompanied by text.